2007
DOI: 10.1016/j.gca.2007.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of elemental release during microbe–basalt interactions at T=28°C

Abstract: This study used batch reactors to characterize the rates and mechanisms of elemental release during the interaction of a single bacterial species (Burkholderia fungorum) with Columbia River Flood Basalt at T = 28°C for 36 days. We primarily examined the release of Ca, Mg, P, Si, and Sr under a variety of biotic and abiotic conditions with the aim of evaluating how actively metabolizing bacteria might influence basalt weathering on the continents. Four days after inoculating P-limited reactors (those lacking P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
97
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 89 publications
14
97
1
Order By: Relevance
“…4) to weather biotite. The mineral weathering efficacy of strains of the Burkholderiales was previously reported for other minerals, such as apatite, basalt, and granite (33,(52)(53). We also revealed that the weathering potential varies greatly depending on the isolates: about 40% of the isolates belonging to the Burkholderia genus did not weather biotite under our experimental conditions (Fig.…”
Section: Resultssupporting
confidence: 83%
“…4) to weather biotite. The mineral weathering efficacy of strains of the Burkholderiales was previously reported for other minerals, such as apatite, basalt, and granite (33,(52)(53). We also revealed that the weathering potential varies greatly depending on the isolates: about 40% of the isolates belonging to the Burkholderia genus did not weather biotite under our experimental conditions (Fig.…”
Section: Resultssupporting
confidence: 83%
“…monoxide as a C and energy source (Dunfield and King, 2004;King and Weber, 2008) or by growing heterotrophically using trace amounts of organic carbon (Cockell et al, 2009;Wu et al, 2007). Studies on the microbiota of volcanic terrains have only emerged within the past few years, revealing that such habitats are capable of harbouring significant microbial diversity, despite their extreme nature (GomezAlvarez et al, 2007;Kelly et al, 2010).…”
Section: Marteinsson Et Al: Microbial Colonization In Diverse Surmentioning
confidence: 99%
“…It is well known that bacteria can obtain nutrients from solid-phase minerals (1,4,5,36,47). Subsurface environments are oligotrophic, and bacteria have been shown to preferentially weather minerals that contain phosphate and ammonia, both required for growth (36,37).…”
mentioning
confidence: 99%
“…Specifically, experiments with basalt and granite have shown that it can weather these rocks and release phosphate into the environment (47,48). Members of the Burkholderia genus have been isolated from granitic soils (48) and have been shown to be efficient at mineral weathering (40).…”
mentioning
confidence: 99%